Improvement in sleep outcomes with a 17β-estradiol–progesterone oral capsule (TX-001HR) for postmenopausal women. Issue 6 (June 2019) - Kagan, Risa; Constantine, Ginger; Kaunitz, Andrew M.; Bernick, Brian; Mirkin, Sebastian
Abstract: Objective: The aim of the study was to evaluate the effects of TX-001HR, a single-capsule 17β-estradiol–progesterone on sleep parameters in postmenopausal women with vasomotor symptoms (VMS) using the Medical Outcomes Study (MOS)-Sleep scale questionnaire in the REPLENISH trial. Methods: In the REPLENISH trial (NCT01942668), women were randomized to one of four doses of TX-001HR or placebo, and the 12-item MOS-Sleep questionnaire (secondary endpoint) was self-administered at baseline, week 12, and months 6 and 12. Changes from baseline in the MOS-Sleep total score and 7 subscale scores were analyzed for treatment groups versus placebo at all time points. Somnolence was also collected as an adverse event. Results: Women (mean age 55 y) were randomized to TX-001HR (estradiol/ progesterone [E2/P4] [mg/mg]) doses: 1/100 ( n = 415), 0.5/100 ( n = 424), 0.5/50 ( n = 421), 0.25/50 ( n = 424), or placebo ( n = 151). TX-001HR significantly improved MOS-Sleep total score, Sleep Problems Index II subscale, and sleep disturbance subscale versus placebo at all time points, except with 0.25 mg E2/50 mg P4 at week 12. Differences in LS mean changes between TX-001HR and placebo for MOS-Sleep total scores ranged from −6.5 to −7.6 at 12 months (all; P ⩽ 0.001). All doses of TX-001HR significantly improved the Sleep Problems Index I subscale at all time points. The sleep somnolence subscale significantly improved from baseline with 0.5 mg E2/100 mg P4 and 0.5 mg E2/50 mg P4 at month 12. The incidence of somnolence as a treatment-emergent adverse event ranged from 0.2% to 1.2% versus 0% with placebo. Conclusion: TX-001HR significantly improved MOS-Sleep parameters from baseline to week 12, which was sustained for up to 12 months, and was associated with a very low incidence of somnolence.